Relationship Between Maternal Height with Children Under Two Years Old Stunting Occurrence - Danubrata, Santika; er, Ernawaty (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT The prevalence of stunting is often used as a marker of child malnutrition at the population level. The height of the mother reflects the previous nutritional and socio-economic status of the mother. This research aims to determine the relationship between maternal height and the incidence of stunting in children under two years old. An analytical study with a case-control study design was conducted based on medical records of mothers and their infants born in 2022 at a health center in Ngawi. This study identified 32 children with stunting were taken as cases and 32 other children with normal nutritional status as control. Maternal height had no association with the incidence of stunting (p=0.210). Adult height varies across countries, the extent to which the prevalence of stunting reflects parental height is also likely to vary. From a policy perspective, it is helpful to distinguish between the prevalence of child stunting attributable to the current environment and that attributable to parental height. Keywords: Maternal Height; Nutritional Status; Stunting